Engineering Performance and Security with Cipherbase - Arasu, Arvind; Blanas, Spyros; Eguro, Ken; Joglekar, Manas; Kaushik, Raghav; Kossmann, Donald; Ramamurthy, Ravi; Upadhyaya, Prasang; Venkatesan, Ramarathnam (Data Engineering Bulletin, 2012)
Cipherbase is a full-fledged relational database system that leverages novel customized hardware to store and process encrypted data. This paper outlines the space of physical design options for Cipherbase and shows how application developers can implement their data confidentiality requirements by specifying the encryption method for static data storage and the acceptable information leakage for runtime data processing. The goal is to achieve a physical database design with the best possible performance that fulfills the application’s confidentiality requirements.